Міжнародна науково-технічна конференція до ювілею - 100-річчя Товариства геодезистів Польщі (SGP) - Тревого, І.; Задорожний, В.; Ванчура, О.; Trevoho, I.; Zadorozhnyy, V.; Vanchura, O. (Видавництво Львівської політехніки, 2019)
Наведено інформацію про міжнародну науково-технічну конференцію присвячену 100-річчю Товариства геодезистів Польщі (SGP), в якій взяли участь майже 400 фахівців, науковців і офіційних осіб з Польщі та багатьох закордонних країн. Серед гостей були президенти Світової федерації геодезистів (FIG), Європейської геодезичної асоціації (CLGE), делегації національних геодезичних товариств Німеччини, України, Чехії, Словаччини, Австрії та інших країн.

It is provided an information about the international scientific c and technical conference to the 100th anniversary of the Polish Society of Geodesy (Stowarzyszenie Geodetów Polskich – SGP) that was attended by almost 400 specialists, scientists and official persons from Poland and many foreign countries. Among the guests were the President of the International Federation of Surveyors (FIG), the Council of European Geodetic Surveyors (CLGE), the delegations of the National Geodetic Societies of Germany, Ukraine, Czech Republic, Slovakia, Austria and other countries.
International scientific and technical conference to the 100th anniversary of the Polish society of geodesy (stowarzyszenie Geodetów Polskich – SGP)
Keywords: конференція; геодезія; ювілей; історія; співпраця; conference; geodesy; anniversary; history; cooperation; 528.04